Dark tourism, abjection and blood: A festival context. (February 2018) - Podoshen, Jeffrey S.; Yan, Grace; Andrzejewski, Susan A.; Wallin, Jason; Venkatesh, Vivek
Abstract: Dark tourism and its implications have been gaining significant prominence in both the literature and in practice in the recent past. Understanding the process and outcomes of dark tourism related to tourists and local hosts can play a key role in relations between the two groups of people. This paper, utilizing long-form interview data and content analysis, examines the psychological processes of some global Jewish citizens in relation to tourism activity and local hosts surrounding historic Holocaust sites located in Eastern and Central Europe. These attribution-oriented processes, which include the group attribution error, the perseverance effect and the role of atypical information generate novel insights into social-psychological activity nested in dark tourism. Our research yields significant implications on collective memory and narrative, representation, authenticity and ownership within the context of dark tourism. Highlights: We find more novel insights and implications that take the study of dark tourism further beyond the historic and educational realms and into a more present-centered orientation. The spaces we have studied are a lived consumption experience with specific subcultural narratives and a quest for extremity relating to the death and darkness. Transitory space acts as important moment in dark tourism experience.